O programa pró-equidade de gênero e raça e o enfrentamento das desigualdades no mundo do trabalho: um estudo a partir dos sentidos construídos pela secretaria de políticas para as mulheres - Ortiz, Marilia Sorrini Peres (2014)
This dissertation discusses the effects of competition in the senses involving affirmative action policies to promote equality of opportunity and treatment between women and men in the formal workplace. To do so, it takes as the object of research the Equality Program of Gender and Race, seeking to reveal the ideas and actions that shapes and moves their intentionality in the Secretariat of Policies for Women (SPM) of the federal government – which is the institution responsible for this policy. The primary sources of the analysis here produced are the narratives of key actresses who participated in the design and implementation of the Program. It was used the Critical Discourse Analysis (CDA) as a methodology and the epistemic context of languages of “affirmative action” and “diversity management” to locate the discursive fields of the accessed narratives. The comprehension of senses is founded on theoretical contributions to the organizational studies that aim to reveal the ideological materiality behind the speeches. Based on Thoenig’s work, (2007) this paper analyzes how the interdependence between different internal and external organizational boundaries to SPM mobilizes the construction of 'standard' that underpins the Equality Program of Gender and Race. Additionally, utilizing the contributions of Crozier (1967), it was shown the 'zones of relevant uncertainty' hanging over the program around decisions taken by the management of SPM. The study suggests that the Pro-Gender Equity Program and Race - taken as a highlighted solution by SPM to dialogue with the formal sector in regarding to the importance of promoting equality of opportunity and treatment in the workplace - negotiates the reverse of its purpose in the long term. Among the reasons for this effect would be the difficulty of the Program to incorporate its priority audience (large corporations) and its contribution to strengthening the speech from parts contrary to the ideology of affirmative action on gender and race in the field of work.